Progression patterns under BRAF inhibitor treatment and treatment beyond progression in patients with metastatic melanoma. (20th December 2017) - Hassel, Jessica C.; Buder‐Bakhaya, Kristina; Bender, Carolin; Zimmer, Lisa; Weide, Benjamin; Loquai, Carmen; Ugurel, Selma; Slynko, Alla; Gutzmer, Ralf; ,
Abstract: Despite markedly improved treatment options for metastatic melanoma, resistance to targeted therapies such as BRAF inhibitors (BRAFi) or BRAFi plus MEK inhibitors (MEKi) remains a major problem. Our aim was to characterize progression on BRAFi therapy and outcome of subsequent treatment. One hundred and eighty patients with BRAF‐mutant metastatic melanoma who had progressed on treatment with single‐agent BRAFi from February 2010 to April 2015 were included in a retrospective data analysis focused on patterns of progression, treatment beyond progression (TBP) and subsequent treatments after BRAFi therapy. Analysis revealed that 51.1% of patients progressed with both new and existing metastases opposed to progression of only preexisting (28.3%) or only new (20.6%) metastases. Exclusive extracranial progression occurred in 50.6% of patients compared to both extra‐ and intracranial (29.4%) or sole cerebral progression (20%). Multivariable analyses demonstrated that single site progression and primary response to BRAFi were associated with improved progression‐free survival. Progression with exclusively new or only existing metastases and a baseline Eastern Cooperative Oncology Group (ECOG) of 0 were associated with prolonged overall survival (OS). TBP had no significant impact on OS. Other subsequent treatments showed low efficacy with the exception of anti‐PD‐1 antibodies. In conclusion we identified specific patterns of progression which significantly correlate with further prognosis after progression on BRAFi treatment. In contrast to previously published data, we could not demonstrate a significant survival benefit for BRAFi TBP. Subsequent therapies had strikingly low efficacy except for PD‐1 inhibitors. Abstract : We identified patterns of progression that significantly correlate with further prognosis after progression on BRAF inhibitor (BRAFi) treatment. In contrast to previously published studies, we did not find a significant survival benefit for BRAFi treatment beyond progression, whereas subsequent therapies (ipilimumab, chemotherapy) had strikingly low efficacy except for PD‐1 inhibitors.